2018
DOI: 10.3390/ijerph15030452
|View full text |Cite
|
Sign up to set email alerts
|

Removal and Biodegradation of 17β-Estradiol and Diethylstilbestrol by the Freshwater Microalgae Raphidocelis subcapitata

Abstract: Natural steroidal and synthetic non-steroidal estrogens such as 17β-estradiol (E2) and diethylstilbestrol (DES) have been found in natural water, which can potentially endanger public health and aquatic ecosystems. The removal and biodegradation of E2 and DES by Raphidocelis subcapitata were studied in bacteria-free cultures exposed to single and mixture treatments at different concentrations for 96 h. The results showed that R. subcapitata exhibited a rapid and strong ability to remove E2 and DES in both sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 62 publications
(77 reference statements)
1
22
0
Order By: Relevance
“…Not much work has been conducted to determine the MIC of E2 against fungi. In a recent study, microalgae, Raphidocelis subcapitata was reported to withstand maximum concentration 3.2 mg L −1 of E2 whereas strain AJAC3, in this study, showed much higher rate of tolerance against the contaminant [25].…”
Section: Minimum Inhibitory Concentrationsupporting
confidence: 42%
“…Not much work has been conducted to determine the MIC of E2 against fungi. In a recent study, microalgae, Raphidocelis subcapitata was reported to withstand maximum concentration 3.2 mg L −1 of E2 whereas strain AJAC3, in this study, showed much higher rate of tolerance against the contaminant [25].…”
Section: Minimum Inhibitory Concentrationsupporting
confidence: 42%
“…The latter is considered to be the strongest among the endocrine factors in the environment [ 10 ]. Synthetic estrogens have been divided into steroidal, such as 17α-ethynylestradiol and 3-methyl ether of ethynylestradiol, used as ingredients of birth control pills, and nonsteroidal estrogens such as diethylstilbestrol used to prevent miscarriages [ 3 , 7 , 11 ]. Human use of the latter was banned in 1972 due to its negative effects, however, it is still used in China as a growth promotor for terrestrial livestock or fish [ 11 ].…”
Section: Endocrine Disrupting Compounds (Edcs) In the Environment mentioning
confidence: 99%
“…This biological activity can lead to low levels of estrogen in the environment causing endocrine disorders in the wildlife population. Negative effects on development, sex differentiation, reproduction of different animal species and production of vitellogenin have been documented [ 3 , 4 , 7 , 11 , 12 ]. Intersexual disorders in fish in Europe, and a negative impact on the sexual behaviour of frogs in suburban areas in the United States have been observed [ 12 ].…”
Section: Endocrine Disrupting Compounds (Edcs) In the Environment mentioning
confidence: 99%
See 2 more Smart Citations